Raising awareness of Alzheimer's clinical trials: Development of messages tailored to African American caregivers and individuals at risk: Public health: Engaging people in ADRD research. (7th December 2020) - McGowan, Melissa; Massett, Holly A; Han, Sae H; Watson, Jennifer; Emmerson, Karen; Burns, Adam; Robinson, Candice Watkins; Hummel, Allyson; Silverberg, Nina; Elliott, Cerise L; Donley, Grayson; Bernard, Marie A
Abstract: Background: Higher rates of Alzheimer's Disease (AD) and related dementias (ADRD) among African Americans compared to non‐Hispanic whites are well‐documented, as is the underrepresentation of African Americans in AD/ADRD clinical research. Key documented impediments to enrollment of African Americans are too few researchers offering studies and limited materials that provide culturally relevant information. This abstract presents findings from focus groups conducted by the National Institute on Aging (NIA) to identify salient, culturally appropriate message concepts that raise awareness, address barriers and motivate African Americans to consider participation in AD/ADRD studies. Method: Nine focus groups (N=65) were conducted among three African American audiences who: 1) have a family history of AD/ADRD; 2) have no family history of AD/ADRD; and, 3) are caregivers of persons with AD/ADRD. Sessions explored participants' knowledge, attitudes, and beliefs about AD/ADRD and AD/ADRD clinical research unaided and in the context of testing multiple message concepts designed to increase interest and encourage individuals to seek information regarding AD/ADRD clinical trials. Result: Message concepts were categorized into three reaction types: positive, negative, and mixed. Concepts that positively increased interest in trials were those that portrayed hope for future generations, connected research with the potential to prevent/treat AD/ADRD, and directly addressed the higher AD/ADRD incidence rates among African Americans. Highlighting the need to find treatments that work for all races was a top motivator to consider a trial. Concepts that decreased interest in trials were those viewed as: being overly emotional; making generalizations about participants' motivations; downplaying the history of medical abuse; and, using conditional language ("one day", "may", "hopefully"). All groups were more receptive to messages that established a realistic, personal connection. Concept visuals will be presented. Conclusion: This research conducted by the NIA improves our understanding of message concepts that are acceptable and motivating and which are unacceptable or inappropriate to African Americans around considering participating in AD/ADRD clinical research. The findings from this study will be used to develop, finalize and make available to the research community a suite of culturally appropriate, well‐tested materials to increase awareness of AD/ADRD and clinical research.